2022
DOI: 10.3389/fnut.2022.931060
|View full text |Cite
|
Sign up to set email alerts
|

Matcha green tea targets the gut–liver axis to alleviate obesity and metabolic disorders induced by a high-fat diet

Abstract: Obesity induced by a high-fat diet (HFD) is an increasing global health problem, leading to many metabolic syndromes. As the emerging food additive rich in tea polyphenols, theanine, caffeine, and so on, matcha green tea has gained more and more popularity for its outstanding potential in ameliorating metabolic disorders. This study investigated the composition and antioxidant activity of matcha green tea and further explored its effects on gut–liver axis homeostasis in an HFD-induced obese mouse model. Male (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…35 Long-term over-consumption of HFD directly induced obesity due to excessive energy and lipid accumulation and contribute to hyperlipidemia, insulin resistance, hyperglycemia, and chronic inflammation. 36 Our data revealed that LAX noticeably reduced the body weights, primarily attributed to a decrease in fat mass rather than lean mass. Interestingly, LAX did not significantly reduce the weights of pWAT.…”
Section: Contentsmentioning
confidence: 55%
See 1 more Smart Citation
“…35 Long-term over-consumption of HFD directly induced obesity due to excessive energy and lipid accumulation and contribute to hyperlipidemia, insulin resistance, hyperglycemia, and chronic inflammation. 36 Our data revealed that LAX noticeably reduced the body weights, primarily attributed to a decrease in fat mass rather than lean mass. Interestingly, LAX did not significantly reduce the weights of pWAT.…”
Section: Contentsmentioning
confidence: 55%
“…Adipose tissue, a central metabolic organ, regulates metabolic homeostasis by storing energy, influencing insulin sensitivity and glucose metabolism, secreting hormones and adipokines, also playing roles in inflammation, lipid metabolism and thermogenesis 35 . Long‐term over‐consumption of HFD directly induced obesity due to excessive energy and lipid accumulation and contribute to hyperlipidemia, insulin resistance, hyperglycemia, and chronic inflammation 36 . Our data revealed that LAX noticeably reduced the body weights, primarily attributed to a decrease in fat mass rather than lean mass.…”
Section: Discussionmentioning
confidence: 99%
“…Total ribonucleic acid (RNA) of intestinal tissues was extracted using the Trizol reagent (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's instructions and our previous study (Y. Wang et al., 2022). The RNA was reversely transcribed using a high‐capacity complementary DNA (cDNA) reverse transcription kit (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…103 The study found that adding 1% matcha green tea to a high-fat diet could improve obesity, fat accumulation, and liver steatosis in rats. 75 The results showed that matcha green tea could reverse the decline of Akkermansia caused by a highfat diet, restore the composition of intestinal microorganisms, and thus restore the BA spectrum of feces. In addition, it was found that apple polyphenols extract, 45,61,94 blueberry extract, 89 cranberry extract, 66 quinoa, 79 flavonoids from wholegrain oat, 71 and xyloglucan compounded inulin 85 could increase the level of Akkermansia and act as an indirect agonist of FXR or TGR5.…”
Section: Reviewmentioning
confidence: 97%